Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa Generasi Z di Universitas Islam Sultan Agung Semarang dengan Konformitas Teman Sebaya sebagai Variabel Intervening - Umi Rahayu; Siti Sumiati (Lembaga Yasin AlSys, 2026)
The consumerist behavior of Generation Z students has become an important issue because it relates to financial management ability, lifestyle patterns, and social influence within peer environments. This study aims to analyze the effect of financial literacy and lifestyle on consumerist behavior, with peer conformity as an intervening variable among Generation Z students at Sultan Agung Islamic University Semarang. This study employed a quantitative approach with an explanatory research method. The research sample consisted of 121 Generation Z students selected using the purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using SmartPLS 4.0. The results show that financial literacy and lifestyle have positive and significant effects on peer conformity and consumerist behavior. In addition, peer conformity also has a positive and significant effect on consumerist behavior. The R-Square value indicates that the research model has fairly good predictive ability. These findings confirm that financial literacy, lifestyle, and peer conformity play important roles in shaping the consumerist behavior of Generation Z students. The implications of this study emphasize the importance of improving financial literacy and controlling lifestyle and social influence so that students are able to manage their finances more wisely.